Plantlet Regeneration From Mature Zygotic Embryo Culture Of Pigeon Pea (Cajanus Cajan L. Mill Sp) Using Thidiazuron - G.P.V SHEKHAR,; M.VENKATESHWARLU,; T. SRILATHA,; K JAGAN MOHAN REDDY,; T. UGANDHAR, (International Journal of Pharma and Bio Sciences, 2012)
We report the plantlet regeneration of ICPL 87119 (Asha) Pigeon pea varieties from mature zygotic embryos cultured in vitro. Mature zygotic embryos were cultured on Murashige and Skoog’s medium augmented with different concentrations of TDZ (1.0 – 6.0 mg/L) Mature Zygotic embryos were germinated and more number of multiple shoot buds are induced directly at 4.0 mg/L followed by 3.0 mg/L and 2.0mg/L TDZ. These multiple shoots were further sub-cultured on the same fresh medium containing 1.0 mg/L TDZ for further elongation. The micro-shoots were transferred onto rooting medium containing MS+0.5-3.0 mg/L IBA and 0.5–3.0 mg/L IAA alone. The micro-shoots were rooted (100%) on MS-medium fortified with 3.0 mg/L IBA. The regenerated plantlets were hardened in Plant Growth Chamber under controlled conditions (humidity 80%; temp.250C). After 3 weeks, plants were transferred to field. The highest percentage of plantlets (95%) was survived under field conditions and they were found to be morphologically identical to the parental plants. Thus in vitro mature zygotic embryo culture plays a role in the production of plantlets that can be transferred to natural field.